2014
DOI: 10.1186/s12284-014-0022-5
|View full text |Cite
|
Sign up to set email alerts
|

Defining the genome structure of `Tongil' rice, an important cultivar in the Korean "Green Revolution"

Abstract: BackgroundTongil (IR667-98-1-2) rice, developed in 1972, is a high-yield rice variety derived from a three-way cross between indica and japonica varieties. Tongil contributed to the self-sufficiency of staple food production in Korea during a period known as the `Korean Green Revolution'. We analyzed the nucleotide-level genome structure of Tongil rice and compared it to those of the parental varieties.ResultsA total of 17.3 billion Illumina Hiseq reads, 47× genome coverage, were generated for Tongil rice. Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…Most of the genes assigned to the three GO categories were mainly involved in metabolic process, cellular process, binding, catalytic activity, cell, and cell part. This functional annotation of genes is consistent with previous findings in rice (Kim et al, 2014;Liu et al, 2017). Additionally, our data showed that the metabolic process involved in the cellular aromatic compound was associated with the common mutated gene cluster ( Figure 5A) and further analyses revealed that nine genes including Badh2 gene having alternative allele's among aromatic group of rice varieties with more than 80% of frequency ( Supplementary Table 8).…”
Section: Discussionsupporting
confidence: 91%
“…Most of the genes assigned to the three GO categories were mainly involved in metabolic process, cellular process, binding, catalytic activity, cell, and cell part. This functional annotation of genes is consistent with previous findings in rice (Kim et al, 2014;Liu et al, 2017). Additionally, our data showed that the metabolic process involved in the cellular aromatic compound was associated with the common mutated gene cluster ( Figure 5A) and further analyses revealed that nine genes including Badh2 gene having alternative allele's among aromatic group of rice varieties with more than 80% of frequency ( Supplementary Table 8).…”
Section: Discussionsupporting
confidence: 91%
“…These indica varieties have a remarkably higher αT content compared to other indica varieties. Genetic backgrounds of the nine special varieties were investigated, and two were tongli-type varieties obtained using a three-way cross of indica/japonica varieties (Chung and Heu 1991;Kim et al 2014). Thus, the japonica alleles in those indica varieties were introduced from the japonica parents via artificial crossing.…”
Section: Discussionmentioning
confidence: 99%
“…ricediversity.org/data/), the HapRice world SNP data (Yonemaru et al 2014) of the Q-TARO database (http://qtaro.abr.affrc.go.jp/), and the resequencing data of 40 rice cultivars from CMB lab. Seoul National University generated using Illumina platform based on methods described by Kim et al (2014). SNPs showing only substitution polymorphism between indica and japonica varieties and no other SNP in at least 60 bp on either side were selected.…”
Section: Snp Selection and Fluidigm Genotype Assay Designmentioning
confidence: 99%